COMPARISON OF FINANCIAL PERFORMANCE USING LIQUIDITY, SOLVABILITY, ACTIVITY AND PROFITABILITY RATIO IN CEMENT SUB SECTOR COMPANIES PERIOD 2014-2019 - Fauji, Ade; Pertiwi, Anada Meli (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2021)
ABSTRACTCompany performance is the achievement achieved by the company in a certain period as a result of work processes during that period. Performance measurement is used by companies to make improvements to their operational activities in order to compete with other companies.The research method used in this research is descriptive qualitative analysis method. The data used in this study are secondary data in the form of annual reports of the cement sub-sector company, the period 2014-2019. The cement sub-sector companies listed on the Indonesia Stock Exchange are as many as 6 companies, while companies that are the object of research are 5 companies.Liquidity ratio based on the current ratio aspect of PT. Semen Indonesia and PT. Wijaya Karya Beton is in an illiquid state because the current ratio is below the average of 2.50 times. Solvency ratio based on the aspect of Debt to Total Assets PT. Holchim and PT. Wijaya Karya Beton is in an insolvable state because its Debt to Asset Ratio is above the average by 38%. Activity ratio based on the aspect of Total Asset Turnover of PT. Holchim and PT. Indocement Putra Prakasa for the 2015-2019 period was above the industry standard of 0.57. Profitability ratio based on the aspect of return on assets of PT. Indocement and PT. Semen Indonesia for the 2015-2019 period was above the industry standard by 5.12%. Semen Baturaja is superior to other cement companies in terms of current ratio and quick ratio. PT. Indocement is superior to other cement companies in terms of debt to asset ratio, debt to equity ratio and return on assets. PT. Wiajaya Karya Beton is superior to other cement companies in terms of total asset turnover and return on equity. PT. Holchim is superior to other companies in terms of inventory turnover. PT. Indocement is superior to other cement companies in terms of return on assets.